Fruit juice concentrate processing plant - Araullo, Gerald B.; Baligod, Melanie L.; Barcelon, Emy A.; Casiason, Rodel C. (Quezon City College of Engineering, 1999)
Product: Calamansi, Pomelo and Passion Fruit Juice Concentrates -- Plant location: Barangay May-it, Lucban, Quezon Province -- Annual volume of production: 600,000 kg -- Annual gross sales: Php 135,000,000.00 -- Annual income: Php 22,116,049.00 -- Total Investment Cost: Php 115,079,380.00 -- Product Unit Cost: Php 145.84 per kg -- Product selling price: Php 205.00/kg pomelo concentrate - Php 245.00/kg calamansi concentrate - Php 225.00/kg passion fruit concentrate -- Return on investment: 19.22% -- Payback period: 2.07 years
Submitted in partial fulfillment of the requirements in ChE 142 Plant Design.
Keywords: Factories -- Design and construction; Concentrated fruit juices